PERAN AUDIT FEE, JASA NON AUDIT, LAMA HUBUNGAN AUDIT DAN UKURAN KAP TERHADAP INDEPENDENSI AUDITOR - Gde Herry Sugiarto Asana; Komang Krishna Yogantara (Badung: LPPM Universitas Triatma Mulya, 2020)
Independence is a free mental attitude and is not controlled by other parties as well as the honesty of Auditors in consideration, formulating and expressing opinions. The purpose of this research is to obtain empirical evidence of the influence of Audit Fee, Non-audit services, old audit relations and size of public accountant office on the Independence of Auditors. The population of this research is the Auditor of the public Accountant office registered in the IAPI Directory in 2019. Data collection is performed using questionnaires. The number of samples in this study was 66 respondents using the purposive Sampling method with the criteria of auditors working at least 1 year. The data analysis technique used was multiple linear regression with the help of SPSS version 25.0 program. The results showed that (1) the Audit Fee significantly affects the independence of the Auditor, (2) Non-Audit services have no significant effect on the independence of the Auditor, (3) The length of the audit relationship has significant effect on the independence of the Auditor, (4) The size of the public Accountant Office has no significant effect on the independence of Auditors. (5) Audit Fee, Non-Audit services, length of audit relationship and size of public accountant office simultaneously have significant effect on the independence of Auditors. Thus, to enhance or maintain independence, auditors should avoid variables that can affect independence.